Exploring Consumption and Effects of Carbonated Soft Drink Among Secondary School Students in Rahim Yar Khan (Pakistan) (Journal of Asian Development Studies, 2024)
This cross-sectional study aimed to evaluate the knowledge, attitudes and practices of secondary school students regarding carbonated drinks in the district of Rahim Yar Khan, Punjab, Pakistan. This study was conducted through a self-reported questionnaire, and 350 students participated in the survey from rural (n=148; 42.29%) and urban areas (n=202; 57.71%). 77.02% of rural students and 84.65% of urban students were aware of carbonated drinks. 31.08% of rural and 44.05% of urban students were mindful of carbonated drinks' components (p=0.014). 16.89% of rural students and 81.76% of urban students were known to know the caloric values of carbonated drinks (p